![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
1个回答
展开全部
cos(α +π/6) - sinα
=cosα * cos(π/6) - sinα * sin(π/6) - sinα
= (√3/2) * cosα - (1/2) * sinα - sinα
= (√3/2) * cosα - (3/2) * sinα
= (√3) * [(1/2) * cosα - (√3/2) * sinα]
= (√3) * [cos(π/3) * cosα - sin(π/3) * sinα]
= (√3) * cos(α + π/3)
= 4√3 /5
可以得到:
cos(α + π/3) = 4/5
α + π/3 = arccos(4/5)
α = arccos(4/5) - π/3
α + π/12 = arccos(4/5) - π/3 + π/12 = arccos(4/5) - π/4
所以,
sin(α + π/12)
=sin[arccos(4/5) - π/4]
=sin[arccos(4/5)] * cos(π/4) - cos[arccos(4/5)] * sin(π/4)
= 3/5 * √2/2 - 4/5 * √2/2
= (-1/5) * √2/2
= - √2/10
所以,正确的答案应该是 B
=cosα * cos(π/6) - sinα * sin(π/6) - sinα
= (√3/2) * cosα - (1/2) * sinα - sinα
= (√3/2) * cosα - (3/2) * sinα
= (√3) * [(1/2) * cosα - (√3/2) * sinα]
= (√3) * [cos(π/3) * cosα - sin(π/3) * sinα]
= (√3) * cos(α + π/3)
= 4√3 /5
可以得到:
cos(α + π/3) = 4/5
α + π/3 = arccos(4/5)
α = arccos(4/5) - π/3
α + π/12 = arccos(4/5) - π/3 + π/12 = arccos(4/5) - π/4
所以,
sin(α + π/12)
=sin[arccos(4/5) - π/4]
=sin[arccos(4/5)] * cos(π/4) - cos[arccos(4/5)] * sin(π/4)
= 3/5 * √2/2 - 4/5 * √2/2
= (-1/5) * √2/2
= - √2/10
所以,正确的答案应该是 B
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询